Dental care to patients using Biposphonates: Case report (Research, Society and Development, 2021)
Osteoporosis is a progressive systemic disease of the skeleton, characterized by reduced bone density and microstructure deterioration of bone tissue. For treatment, the use of bisphosphonates (BFFs) has been recommended as the first choice anti-resorptive therapy. The objective of this work is to describe, through a case report, a dental care protocol for a patient with Osteoporosis and using BFs. The work was submitted and approved by the Research Ethics Committee (CEP), opinion No.: 3.646.508/2019. Female patient, 30 years old, black, with osteoporosis, was referred for dental treatment. At the time of the Anamnesis, he reported using Alendronate Sodium 70mg/day. After clinical examination, laboratory tests for CTX-I dosage and radiographic evaluation, the suggested treatment plan was presented: clinical crown augmentation surgery and subsequent endodontic treatment and oral rehabilitation of tooth 25, which was promptly approved by the patient and signed the Informed Consent Term (TCLE). One week before the surgical procedure for clinical crown augmentation, the suspension of Alendronate sodium was requested. After the endodontic treatment, the prosthetic rehabilitation was carried out, restoring the masticatory and aesthetic function of the teeth, restoring the patient's self-esteem. It was concluded in the present study that it is possible to carry out the dental treatment of patients in bisphosphonate therapy safely, if a well-conducted and detailed anamnesis is carried out and safe treatment protocols are adopted, always aiming at the quality of life and patient satisfaction.